PENAMBAHAN DEKOMPOSER SEBAGAI BAHAN STIMULATOR UNTUK MENINGKATKAN EFEKTIVITAS PESTISIDA NABATI - Julianus Juli; Sri Wahyuni (AGRICA, 2020)
Addition of Decomposers as Stimulators for Increasing the Effectiveness of Vegetable Pesticides. This study aims to determine the increased effectiveness of plant-based pesticides added with several types of decomposers. This study uses a Completely Randomized Design (CRD), with 5 treatments and 5 replications namely: FO: Control (water), F1: Plant pesticides without the addition of decomposers, F2: Vegetable pesticides + EM-4, F3: Vegetable Pesticides + Promi, F4 : Vegetable Pesticides + rice washing water. Observation variables consisted of mortality of contact poison, stomach poison, Lethal Time (LT 50%) and the speed of death as well as the attitudes and eating behavior of Parmarion martency. The results showed an increase in the effectiveness of plant-based pesticides that were significantly different from the control but not significantly different in each treatment where F3 treatment increased mortality by 0.05% (contact poison) from pesticide extracts without the addition of decomposers while the effectiveness of stomach poison only increased by 0, 14%. The fastest 50% lethal time in F3 treatment with 50% LT period was 48.4 hours with a mortality rate of 0.8 hours / individual in contact poison and 50% LT in stomach poison for 52.0 hours with a death rate of 0.6 hours /individual. Changes in behavior due to contact poisons are characterized by releasing grayish white fluid and then death is characterized by a rigid body that is easily reversed, and stomach poisoning behavior is characterized by experiencing less active, being in one place and dying in reverse.